The Real Meaning of Documentary - Florance Yap, ak. Ayu. (Universiti Malaysia Sarawak, (UNIMAS), 2006)
My thesis is entitled "The Real Meaning of Documentary". My final year project resolves in the life of a family who runs a hawker business. This documentary brings us through the journey of the meaning of life as a family as we venture into their personal side of view. This piece also leads us into the perspective of hawker's daughter and her life.